The influence of incident management teams on the deployment of wildfire suppression resources - Hand, Michael; Katuwal, Hari; Calkin, David E.; Thompson, Matthew P. (International journal of wildland fire, 2017)
Despite large commitments of personnel and equipment to wildfire suppression, relatively little is known about the factors that affect how many resources are ordered and assigned to wildfire incidents and the variation in resources across incident management teams (IMTs). Using detailed data on suppression resource assignments for IMTs managing the highest complexity wildfire incidents (Type 1 and Type 2), this paper examines daily suppression resource use and estimates the variation in resource use between IMTs. Results suggest that after controlling for fire and landscape characteristics, and for higher average resource use on fires in California, differences between IMTs account for ~14% of variation in resource use. Of the 89 IMTs that managed fires from 2007 to 2011, 17 teams exhibited daily resource capacity that was significantly higher than resource use for the median team.